The lottery rose - Hunt, Irene (New York : Berkley Books, 1996)
A young victim of child abuse gradually overcomes his fears and suspicions when placed in a home with other boys.
Booklist.
6.0
Young Adult
Keywords: Child abuse -- Fiction; Child abuse -- Fiction